Utility of hybrid PET/MRI multiparametric imaging in navigating SEEG placement in refractory epilepsy. (October 2020) - Zhang, Miao; Liu, Wei; Huang, Peng; Lin, Xiaozhu; Huang, Xinyun; Meng, Hongping; Wang, Jin; Hu, Kejia; Li, Jian; Lin, Mu; Sun, Bomin; Zhan, Shikun; et al.
Highlights: Hybrid PET/MRI is a new technology combined metabolism and morphological imaging. Hybrid PET/MRI increase precisely localizing seizure onset zone (SOZ) in epilepsy. Hybrid PET/MRI optimize SEEG electrode placement. Concordant of PET/MRI and SEEG SOZ location demonstrates favorable surgery outcome. Abstract: Purpose: Stereo-electroencephalography (SEEG) implantation before epilepsy surgery is critical for precise localization and complete resection of the seizure onset zone (SOZ). Combined metabolic and morphological imaging using hybrid PET/MRI may provide supportive information for the optimization of the SEEG coverage of brain structures. In this study, we originally imported PET/MRI images into the SEEG positioning system to evaluate the application of PET/MRI in guiding SEEG implantation in refractory epilepsy patients. Materials: Forty-two patients undergoing simultaneous PET/MRI examinations were recruited. All the patients underwent SEEG implantation guided by hybrid PET/MRI and surgical resection or ablation of epileptic lesion. Surgery outcome was assessed using a modified Engel classification one year (13.60 ± 2.49 months) after surgery. Areas of SOZ were identified using hybrid PET/MRI and concordance with SEEG was evaluated. Logistic regression analysis was used to predict the presence of a favorable outcome with the coherence of concordance of PET/MRI and SEEG. Results: Hybrid PET/MRI (including visual PET, MRI, plus MI Neuro) identified SOZ lesions in 38 epilepsy patients (90.47 %). PET/MRI showed the same SOZ localization with SEEG in 29 patients (69.05 %), which was considered to be concordant. The concordance between the PET/MRI and SEEG findings was significantly predictive of a successful surgery outcome (odds ratio = 20.41; 95 % CI = 2.75–151.4, P = 0.003**). Conclusion: Hybrid PET/MRI combined visual PET, multiple sequences MRI and SPM PET helps identify epilepsy lesions particularly in subtle hypometabolic areas. Patients with concordant epileptic lesion localization on PET/MRI and SEEG demonstrated a more favorable outcome than those with inconsistent localization between modalities.